Chimeric DNA-templated silver nanoclusters as new fluorogenic probes for biosensing applications - Lee, Shi Ting (2019)
Over a decade of research on DNA-templated silver nanoclusters (DNA-AgNCs), this material has now been recognised as an alternative to the conventional fluorescent probes (i.e. quantum dots and organic fluorophores). The DNA-AgNCs have been widely reported for biosensing application due to their design versatility and easy integration with functional DNA sequences. Notwithstanding, a good DNA-AgNCs design is crucial to generate a successful sensing result. Among all of the reported designs, chimeric DNA-AgNCs, i.e. placing AgNCs nucleation sequence and functional sequence in a single DNA strand, is relatively underexplored. This is because the chimeric DNA-AgNCs often exhibit fluorescence turn-off response whereby its accuracy could be affected by false results. However, the simplicity of the chimeric design deserves further investigation, considering it is more cost-effective and enables conclusive results on principles of detection.